The study of morphology of heteroepytaxial structures on the basis of photosensitive layers CdXHg1-XTe by electron probe analysis methods - А. С. Kashuba; A. V. Zablotsky; E. V. Korostylev; A. A. Kuzin; E. V. Permikina; V. V. Arbenina (Тонкие химические технологии, 2010)
Data of morphology of epitaxial layers CdXHg1-XTe, which has been grown on substrates GaAs (310) by MBE, have been presented. Peculiarities of growing V-defects have been studied by scanning electronic microscopy techniques and EDS. The structure, orientation, chemical composition of V-defects, causes of appearance and formation have been studied.